Bayesian analysis of econometric time series models using hybrid integration rules - Ajax Reynaldo Bello Moreira; Dani Gamerman (Institute for Applied Economic Research (ipea), 2015)
This paper is concerned with the study of Bayesian inference procedures to commonly used time series models. In particular, the dynamic or state-space models, the time-varying vector autoregressive model and the structural vector autoregressive model are considered in detail. Inference procedures are based on a hybrid integration scheme where state parameters are analytically integrated and hyperparameters are integrated by Markov chain Monte Carlo methods. Credibility regions for forecasts and impulse responses are then derived. The procedures are illustrated in real data sets.
Keywords: 330; Bayesian; Dynamic; Hyperparameters; Impulse response; Markov chain Monte Carlo; Metropolis-Hastings algorithm; Vector autoregressive models